2008
DOI: 10.2320/matertrans.t-mra2007882
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Mechanical Properties of Composite Structure by Warm Spraying of Zr-Base Metallic Glass

Abstract: Metallic glasses are highly attractive because of their superior strength, relatively low Young's modulus and superb corrosion resistance[S1], etc. By combining a metallic glass with different materials, synergy effect can be expected in the mechanical properties and corrosion resistance, for example. Fabricating a thick metallic glass layer on a substrate material by thermal spray process is one way to bond these materials. In such practice, however, the temperature of the sprayed metallic glass and that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The feedstock powder was amorphous, with no obvious peaks except the hallow peak at approximately [30][31][32][33][34][35][36][37][38][39][40] • . The deposit prepared by warm spraying shows very small peaks assigned to ZrO 2 .…”
Section: Metallic Glass [32]mentioning
confidence: 99%
“…The feedstock powder was amorphous, with no obvious peaks except the hallow peak at approximately [30][31][32][33][34][35][36][37][38][39][40] • . The deposit prepared by warm spraying shows very small peaks assigned to ZrO 2 .…”
Section: Metallic Glass [32]mentioning
confidence: 99%
“…Microstructure and mechanical properties of WS coatings have been investigated for materials such as titanium, copper, aluminum, metallic glass, WC-Co cermet, nanograin titanium oxide, UHMW-PE, and PEEK (Watanabe et al, 2007a,b;Chivavibul et al, 2008Chivavibul et al, , 2010Kawakita et al, 2008b;Kim et al, 2008Kim et al, , 2009aKim et al, ,b,c, 2010a. Among them, titanium and WC-Co have been most extensively studied due to their potential application importance and sensitivity to thermal degradation.…”
Section: Microstructure and Mechanical Properties Of Ws Metallic Coatmentioning
confidence: 99%
“…Compared to the cold spray deposition, this technique provides a capability to control the temperature of sprayed particles in a wide range. The success of using this technique to deposit various materials (Ref [17][18][19][20] such as titanium and metallic glass has been reported. Recently, Watanabe et al (Ref 11,18) demonstrated a capability of this technique to deposit WC-12Co coating.…”
Section: Introductionmentioning
confidence: 96%